Observer-Based Output Feedback Tracking Consensus for Multi-Agent Systems With Periodic Intermittent Communication and Input Saturation - Yiping Luo; Beining Bao; Jinde Cao (IEEE Access, 2023)
This paper studies the semi-global tracking consensus problem for general multi-agent networks with input saturation and periodic intermittent communication. The considered problem is solved by proposing an efficient distributed observer-based periodic intermittent control protocol, where the control inputs of follower agents are subjected to saturation. First, a low-gain feedback method is introduced to suppress the input saturation constraint, and the output feedback control protocol for agents are defined based on the algebraic Riccati equation. Next, a state observer is designed to ensure that observer can realize state reconstruction under the condition that the state of agents cannot be measured directly in the process of information interaction. Then, according to the Lyapunov second method and related linear inequalities, the sufficient conditions which are necessary for a state observation system for the coordinated tracking consensus, are defined under the conditions of input saturation and periodic intermittent communication. Finally, a simulation is performed to prove the expectant algorithm.